(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2012)
Four vertebral centra from the well known fossil-bearing Prezzo Limestone (Upper Anisian, Middle Triassic) at the newly discovered locality Piazza Brembana (Bergamo) are described. The four bones were found exposed on the bed surface in an articulated position. Despite the incompleteness of three centra due to erosion, their otherwise fairly good preservation facilitated their study and attribution to a shastasaurid ichthyosaur. Even though the classification of isolated vertebral centra at the genus level is controversial, the presence of diapophyses truncated by the cranial margin of the centra is still considered to be diagnostic for Cymbospondylus. The new discovery comes from an ammonoid-bearing facies, which is not unusual for ichthyosaurs, and the bio-chronostratigraphic position of the Piazza Brembana bones is accurately defined by ammonoids from the lowest part of the Trinodosus Zone (Illyrian, Middle Triassic). Records of Cymbospondylus in the Southern Alps, Germanic Basin, western United States and Spitsbergen are summarized and all previous occurrences of the genus are bio-chronostratigraphically correlated by utilizing the abundant ammonoid literature. The single occurrence of Phantomosaurus neubigii is also considered, since this species is regarded in the literature as the sister taxon of Cymbospondylu. Material referred to Cymbospondylus extends from a single occurrence in the Olenekian (late Early Triassic) to the Longobardian (Late Ladinian), and its stratigraphic distribution is strictly controlled by the development of basins. Within these basins the distribution of specimens appears to include relatively protected and shallow waters. Such a distribution is consistent with the mode of life of this group of ichthyosaurs as suggested by morphofunctional analysis. Cymbospondylus, like most Triassic Ichthyosaurs, probably was an undulatory swimmer, more maneuverable but slower than their Jurassic successors.